2012
DOI: 10.1186/1472-6882-12-155
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multi-herb supplement for erectile dysfunction: a randomized double-blind, placebo-controlled study

Abstract: BackgroundEvidence is lacking for multi-ingredient herbal supplements claiming therapeutic effect in sexual dysfunction in men. We examined the safety and efficacy of VigRX Plus (VXP) – a proprietary polyherbal preparation for improving male sexual function, in a double blind, randomized placebo-controlled, parallel groups, multi-centre study.Methods78 men aged 25–50 years of age; suffering from mild to moderate erectile dysfunction (ED), participated in this study. Subjects were randomized to receive VXP or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…In this regard, some studies have reported its beneficial effects 7,8 and free radical scavenging by ginkgo has been suggested as a possible mechanism. 31,41 However, others have found no such effect. [9][10][11][12] Our findings do not confirm the studies reporting the effectiveness of Ginkgo biloba in treating memory impairments due to its antioxidant properties, 42,43 but are in agreement with those reports showing that the retention deficit caused by ischemia was not statistically reduced by ginkgo extract.…”
Section: Figmentioning
confidence: 99%
“…In this regard, some studies have reported its beneficial effects 7,8 and free radical scavenging by ginkgo has been suggested as a possible mechanism. 31,41 However, others have found no such effect. [9][10][11][12] Our findings do not confirm the studies reporting the effectiveness of Ginkgo biloba in treating memory impairments due to its antioxidant properties, 42,43 but are in agreement with those reports showing that the retention deficit caused by ischemia was not statistically reduced by ginkgo extract.…”
Section: Figmentioning
confidence: 99%
“…Moreover, Shah et al () documented that erectile dysfunction or impotence which can be defined as the insistent failure to attain and maintain an erection sufficient for sexual satisfactory. It is classified as one of the oldest diseases well known to mankind, it affects more than 52% of 40‐ to 70‐year‐old men globally, with a projection of over 320 million by the year 2025 (Shah et al, ). Clinically, in the treatment of erectile dysfunction, drugs such as Staxyn, Viagra, and Levitra are used.…”
Section: Introductionmentioning
confidence: 99%
“…Many pharmacological and clinical studies have shown that the extract of Gingko causes two main actions: increase of blood flow in central and peripheral vessels and inhibition of platelet aggregation and free radical scavenging. Thus Gingko may be effective in cases of erectile dysfunction due to a decreased blood flow [26]. …”
Section: Introductionmentioning
confidence: 99%